Tourist Perceptions of Product Diversification at Beach Clubs in Badung Regency, Bali-Indonesia - Putu Diah Kesumadewi; A.A Manik Pratiwi; Ni Putu Ariningsih; Trisna Putra (Faculty of Economics and Business, University of Mataram, 2026)
This research analyzes tourist perceptions of beach club service products in Badung Regency, focusing on four key dimensions: food quality, service quality, atmosphere, and pricing. The study aims to examine how these components collectively shape visitor evaluations within experiential tourism settings. A descriptive quantitative design was employed, with data collected through Likert-scale questionnaires completed by 100 beach club visitors in Badung Regency. The instrument measured perceptions across four variables operationalized from established hospitality and tourism literature. Descriptive statistical analysis was used to calculate mean scores and identify patterns in perceptions. All dimensions received positive evaluations within the â€œagreeâ€ category. Atmosphere recorded the highest mean score (4.23), followed by service quality (4.07), food quality (4.04), and pricing (3.86). The findings indicate that experiential elements particularly ambiance and interpersonal service interactions are the primary determinants of visitor satisfaction, while pricing remains the most sensitive dimension. Beach clubs in Badung Regency successfully deliver experience-oriented services that align with contemporary leisure tourism trends. The results underscore the importance of maintaining consistent, immersive service design to strengthen competitiveness in the coastal tourism industry. This research contributes to understanding behavioral tendencies in beach club tourism and provides insights for improving service strategies.